Commercial pesticide application complaints - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet discusses the process of a commercial pesticide application complaint.
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides; Pesticide applicators (Persons); Complaints (Administrative procedure)